PENGARUH PARAMETER PROSES TERHADAP UJI IMPAK PADA 3D PRINTING MATERIAL ABS - Rully Febriansyah; Adhe Anggry; Pristiansyah Pristiansyah (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Technology 3D printing is also known as Additive Layer Manufacturing. One of the most well-known 3D printing technologies is Fused Deposition Modelling (FDM). The working principle of FDM is by means of thermoplastic extrusion through the nozzle at the melting temperature then the product is printed perlapis layer. This research filament used is ABS (Acrylonitrile Butadiene Styrene) because mechanically this filament is very strong and has resistance to high temperatures, for the factors used namely Infill Layer Thickness, Printing Speed, Wall Thickness, Print Temperature, Bed Temperature, Fan Speed Wall Printing Speed, Infill Overlap, While in this study the method used is Taguchi and this study has the aim to get optimal process parameters on Printing impact tests were conducted with a 3D printing machine Creality Ender 3 printed as many as 81 specimens. Then the impact test was conducted so that the average score of the highest impact test result was in experiment number 27 with a value of 0.00392 joules and for the lowest impact test value was in experiment number 1 with a value of 0.00291 Joule.